Factors underlying competitive success in youth football: A study of the Swedish national U15 football talent system - Söderström, T.; Brusvik, P.; Lund, S. (Scandinavian Sport Studies Forum, 2019)
This study of Sweden`s 24 football districts analyses whether contextual factors (number of players, number of elite teams, and number of elite players on each district team) influence the district teams` relative age effect (RAE) and the way in which contextual factors and RAE correlate with the U15 teams` competitive success. The analysis is based on register data on district players (4,516 girls and 4,501 boys, all 15 years old) who attended an annual elite football camp: birthdate, the total number of players aged 15, club membership, senior elite clubs, proportion of elite players on the district teams, and match outcomes. Based on the birthdates of the players born between 1986 and 1997, a relative age index was constructed for each district. The results showed a relative age effect (RAE) for the selected district players (boys and girls) compared to the general 15-year-old football population; however, birthdate only affected the competitive success of the boys` district teams. The analysis points out that contextual factors such as the number of football players and the presence of elite clubs are important to consider in order to understand how RAE is produced and its relationship to the success of winning matches for boys` district teams.